Interactions of Guanine with Cr(VI), Ag(I), Cd(II) and Hg(II) in Acidic Aqueous Medium - Shaikh, AA; Paul, Dilip K; Rahman, MS; Bakshi, Pradip K (Journal of the Bangladesh Chemical Society, 2012)
Guanine forms compounds with Cr(VI), Ag(I), Cd(II) and Hg(II) in acidic aqueous media. The compounds are formulated as (C5H6N5O)2(Cr2O7).H2O, [Ag{(C5H6N5O)(NO3)}2](C5H6N5O)(NO3)2, [(C5H4N5O)2Cd](C5H6N5O)Cl and [(C5H4N5O)2Hg](C5H6N5O)Cl on the basis of their metal and chloride contents. Physico-chemical properties such as solubility, melting point, IR and UV-visible spectra, magnetic susceptibility, and thermal behavior of the compounds were studied. The composition of (C5H6N5O)2(Cr2O7).H2O was also investigated by continuous variation method. Keywords: Nucleic acids; Guaninium ions; Pyrimidine ring; Magnetic susceptibilities. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9699 Journal of Bangladesh Chemical Society, Vol. 24(2), 106-114, 2011